EXTRACTION OF PALM OIL’S FREE FATTY ACIDS BY TRIETHYLAMMINE (TEA) IN POLAR-NONPOLAR MIX-SOLVENT - Endang Astuti; Winarto Haryadi; Sabirin Matsjeh (Universitas Gadjah Mada, 2002)
Palm oil contains unsaturated fatty acids that can be oxidated and can make rancidity of the palm oil. One of the trigliserida degradation products is free fatty acid. The usage of triethylammine (TEA) in the polar-nonpolar mix solvents could enhance the free fatty acids extraction efficiency. Free fatty acids extraction from palm oil was carried out for a minute with solvents ratio: TEA 0,00-0,20M in the following solvent: 0-99% diethyl ether + 99-0% ethanol + 1% water, % volume. The extraction was also performed in the following solvent: TEA 0,00-0,20M in 0-95% heptane + 95-0% isopropanol + 5% water, % volume. Reextraction was conducted for a minute by adding Na2SO4 1M. The alcohol layer which was rich with free fatty acid was taken out and the acid value was determined. As comparison, palm oil's free fatty acids was taken out with standard method by refluxing the sample in 95% alcohol for ten minutes. Identification of the free fatty acids was done by Gas Chromatography-Mass Spectrometer. The best solvent ratio for acid value determination was TEA 0,10-0,20M in the mix-solvent: 19% diethyl ether + 80% ethanol + 1% water, % volume and the extraction product contained 8 kind of free fatty acids. In addition, TEA 0,01M in the solvent: 95% isopropanol + 5% water, % volume could be obtained 8 kind of free fatty acids too. In contrary, the free fatty acid extraction by standard method contained 7 kind of fatty acids. Linoleic acid was the free fatty acid which could not be taken out by standard method. The usage of TEA in the proper polar-non polar mix-solvent was the complete method to determine free fatty acid contained in the palm oil.